2008
DOI: 10.1007/s10350-008-9232-5
|View full text |Cite
|
Sign up to set email alerts
|

A Desmoid Tumor-Staging System Separates Patients with Intra-Abdominal, Familial Adenomatous Polyposis-Associated Desmoid Disease by Behavior and Prognosis

Abstract: Desmoid staging identifies tumors by prognosis and its use for designing prospective treatment studies is reasonable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 11 publications
1
53
0
4
Order By: Relevance
“…This tumor behavior has been historically labelled as "locally malignant" [4]. Church reported a 10% spontaneous resolution rate of DTs, and a 10% rapid progression rate, while 50% remain stable on follow up and 30% have cycles of progression and resolution [4,19]. Little is known about the natural history of pancreatic DTs; most (give the n) were resected and the two deaths reported in the literature were not treated with surgery.7 Pancreatic DTs are hard to diagnose preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…This tumor behavior has been historically labelled as "locally malignant" [4]. Church reported a 10% spontaneous resolution rate of DTs, and a 10% rapid progression rate, while 50% remain stable on follow up and 30% have cycles of progression and resolution [4,19]. Little is known about the natural history of pancreatic DTs; most (give the n) were resected and the two deaths reported in the literature were not treated with surgery.7 Pancreatic DTs are hard to diagnose preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, in over 100 FAP patients with desmoid disease, 10% experienced complete regression of their tumor and 7% died from aggressive, unresponsive disease; the remaining 83% experienced variable growth but were not severely affected. 14 …”
Section: Clinical Coursementioning
confidence: 99%
“…The role of endocrine factors in the pathogenesis are supported by clinical observations such as the female predominance, regular occurrence in the childbearing age, progression via the use of oral contraceptives, and regression in post-menopausal or post-oophorectomy patients or those undergoing antiestrogen therapy (8,11,15,25). An antecedent history of trauma to the site of the tumors, often surgical in nature (prophylactic proctocolectomy, Cesarean section), has been identified in about 25% of cases (5,27,30,33).…”
Section: Etiologymentioning
confidence: 99%
“…It is characterised not only by tumor growth, proliferation, and disease progression but also by stabilization and spontaneous remission (2,7,8,11,25,28,29). Church et al (2008) found that 10% of agressive fibromatoses resolved spontaneously, 30% were unpredictably interchanging between progression and resolution, 50% remained stable following diagnosis, and 10% were characterised by rapid progression (30). Variant desmoid growth patterns have been identified: some progress rapidly and aggressively whereas others are more indolent and may remain stable (2,8,11,15).…”
Section: Clinical Behaviourmentioning
confidence: 99%
See 1 more Smart Citation